Beneficiamento local da produção extrativista e agroflorestal: o caso da Cooperativa Agroextrativista de Xapuri – CAEX - MICHELOTTI, Fernando (2012)
The main purpose of this paper is to elucidate the difficulties faced by Cooperativa Agroextrativista de Xapuri (Xapuri Agroextrativist Cooperative) to achieve its economical viability. Created in 1988 by the rubber tapers from Xapuri (Acre/Brazil), its case study provides an interesting example of an attempt to establish a local agro-extrativist production processing project. This project aimed to aggregate value by processing its members´ Brazil nuts production. The economical return of this iniciative, however, turned out to be less than the expected. Most of the studies dealing with the evaluation of these poor economical results identified as the main causes isolated socioeconomical factors happening in the production and comercialization process. Using conceptual framework of the evolutionary economy,this study pursues the identification of others structural problems as the primary causes leading to this bad economical return.